APAKAH TUNTUTAN PEKERJAAN DAN STRES KERJA PENENTU TURNOVER INTENTION AUDITOR PADA BEBERAPA KAP DI JAKARTA - Danira Reggie Pattinasarany (Jurnal Manajemen, 2019)
This study aims to analyze the effect of job demands, job satisfaction, and job stress on intention to leave work (turnover intention). This study also intends to study the role of job satisfaction and job stress variables in mediating the relationship between job demands and turnover intention. Respondents of this study consist of 50 senior- and junior auditors who are working at the Public Accounting Firms (KAP) and have a maximum of 5-year working experience. The data was solicited through a research questionnaire written in Google forms, where link to the questionnaire was distributed to the respondents by email and WhatsApp. Path analysis is used in analyzing the data following the single-step multiple-mediator model which was introduced by Preacher & Hayes, while data processing is performed using SPSS 21. The results found a significant positive effect of job demands on turnover intention mediated by work stress. Nevertheless, as job demands did not directly affect turnover intention, the relationship between the two occurred only through work stress. These findings indicate that the high job demands faced by auditors working at the KAP will increase work stress. Furthermore, the high level of work stress will increase their desire to leave work (or to increase turnover intention).